Exposure to chronic alcohol accelerates development of wall stress and eccentric remodeling in rats with volume overload. (August 2016) - Mouton, Alan J.; Ninh, Van K.; El Hajj, Elia C.; El Hajj, Milad C.; Gilpin, Nicholas W.; Gardner, Jason D.
Abstract: Chronic alcohol abuse is one of the leading causes of dilated cardiomyopathy (DCM) in the United States. Volume overload (VO) also produces DCM characterized by left ventricular (LV) dilatation and reduced systolic and diastolic function, eventually progressing to congestive heart failure. For this study, we hypothesized that chronic alcohol exposure would exacerbate cardiac dysfunction and remodeling due to VO. Aortocaval fistula surgery was used to induce VO, and compensatory cardiac remodeling was allowed to progress for either 3 days (acute) or 8 weeks (chronic). Alcohol was administered via chronic intermittent ethanol vapor (EtOH) for 2 weeks before the acute study and for the duration of the 8 week chronic study. Temporal alterations in LV function were assessed by echocardiography. At the 8 week end point, pressure-volume loop analysis was performed by LV catheterization and cardiac tissue collected. EtOH did not exacerbate LV dilatation (end-systolic and diastolic diameter) or systolic dysfunction (fractional shortening, ejection fraction) due to VO. The combined stress of EtOH and VO decreased the eccentric index (posterior wall thickness to end-diastolic diameter ratio), increased end-diastolic pressure (EDP), and elevated diastolic wall stress. VO also led to increases in posterior wall thickness, which was not observed in the VO + EtOH group, and wall thickness significantly correlated with LV BNP expression. VO alone led to increases in interstitial collagen staining (picrosirius red), which while not statistically significant, tended to be decreased by EtOH. VO increased LV collagen I protein expression, whereas in rats with VO + EtOH, LV collagen I was not elevated relative to Sham. The combination of VO and EtOH also led to increases in LV collagen III expression relative to Sham. Rats with VO + EtOH had significantly lower collagen I/III ratio than rats with VO alone. During the acute remodeling phase of VO (3 days), VO significantly increased collagen III expression, whereas this effect was not observed in rats with VO + EtOH. In conclusion, chronic EtOH accelerates the development of elevated wall stress and promotes early eccentric remodeling in rats with VO. Our data indicate that these effects may be due to disruptions in compensatory hypertrophy and extracellular matrix remodeling in response to volume overload. Highlights: Volume overload (VO) produced compensatory hypertrophy in rats. Rats with VO given chronic alcohol exhibited increased cardiac wall stress. Alcohol prevented the compensatory hypertrophy response to VO. Combined VO and alcohol produced diastolic dysfunction with ECM alterations. Alcohol abuse may accelerate decompensation of the stressed heart.